2019
DOI: 10.1016/j.actbio.2019.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cell-free and growth factor-free hydrogel capable of inducing angiogenesis and innervation after subcutaneous implantation

Abstract: delayed or impaired recovery of bone defects. The design of innovative biomaterials should improve the host capacity of healing to restore a functional tissue, taking into account that the nerve systems closely interact with blood vessels in the bone tissue. The aim of this work is to develop a cell-free and growth factor-free hydrogel capable to promote angiogenesis and innervation. To this end, we have used elastin-like polypeptides (ELPs), poly(ethylene glycol) (PEG) and increasing concentrations of the adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 65 publications
0
45
0
Order By: Relevance
“…We also noted a volume reduction of EndoECM over time. The degradation and colonization of the scaffold by the endogenous host cells are important properties for materials with biomedical applications, allowing the reconstitution of native tissue (Wua et al, 2015;Naahidi et al, 2017;dos Santos et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We also noted a volume reduction of EndoECM over time. The degradation and colonization of the scaffold by the endogenous host cells are important properties for materials with biomedical applications, allowing the reconstitution of native tissue (Wua et al, 2015;Naahidi et al, 2017;dos Santos et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several fragments of the LN sequence were recently identified and tested for their potential bioactivity, with IKVAV (Ile-Lys-Val-Ala-Val) shown to selectively promote SC migration in vitro and capable of easy conjugation to SAPs 23 , 24 . The functional peptide motif IKVAV is commonly used in neurotrophin releasing and stem cell loading during treatment of traumatic brain injury, spinal cord injury, and sciatic nerve injury due to its ability to enhance cell survival and adhesion, neurite outgrowth, and even angiogenesis 25 - 27 . BDNF is a member of the neurotrophin family and enhances myelination in SCs, promotes neuronal survival and neurite outgrowth, and prevents neural death 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, Santos et al with 50% IKVAV showed complex networks of longer neurites compared to the other incubation compositions. However, the same incubation conditions induced angiogenesis and innervation encircling the implant without the presence of inflammation in the subcutaneous graft [194].Innate small molecules can be sequestered to regulate various cellular activities in vitro,but using the native small molecules for tissue repair in vivo is reported rarely.Recently,the strategy of sequestration of extracellular adenosin has been showed.By levering the affinity of boronate molecule with adenosine and its transient surge following tissue injury,a synthetic biomaterial showed the sequestration of innate adenosine and the acceleration of bone repair in the fracture site of a murine model [195].…”
Section: Other Acellular Bone Scaffold Materialsmentioning
confidence: 99%